Hubungan Antara Role model Perawat Dengan Ketepatan Identifikasi Pasien Di Rumah Sakit Islam Sultan Agung Semarang - Olivia Diah Putri; Muh Abdurrouf; Dyah Wiji Puspita Sari (Jurnal Intelek Insan Cendikia, 2026)
This study aimed to determine the relationship between nurses’ Role model  and the accuracy of patient identification. this study used a quantitative design with a cross-sectional approach. data were collected through questionnaires from 94 nurses inpatient wards using total sampling technique. data were analyzed using the spearman rank correlation test. were analyzed using the spearman rank correlation test. most respondents were aged 31–35 years (39.4%), female (77.7%), held a professional nursing degree (47.9%), and had 3–8 years of experience (40.4%). most nurses had a good Role model  (45.7%) and good patient identification accuracy (43.6%). the statistical test showed a significant relationship between nurses’ Role model  and patient identification accuracy (p = 0.000; r = 0.527), indicating a positive and moderate correlation. there is a significant relationship between nurses’ Role model  and patient identification accuracy   Keywords: Role model , Patient Identification Accuracy, Patient Safety